Evaluation of Univariate Integrals via Fluctuationlessness Theorem - (:unkn) unknown (AMER INST PHYSICS, 2008)
A recently developed Fluctuation Method is used in approximating the remainder term of the integral of the Taylor expansion. This provides us with a new numerical integration method.
Keywords: Numerical Integration; Taylor Polynomials; Fluctuation Expansion; EXPANSION